ANALISIS SEMIOTIK PADA ALBUM “MANUSIA” KARYA TULUS - Sherly Rizki Permatahati; Mohammad Kanzunnudin; Nur Alfin Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the structure and semiotic meanings of the lyrics in Tulus’salbum Manusia, which consists of ten songs reflecting themes of love, loss,meaning, and hope. The lyrics are not only entertaining but also convey deep lifevalues. Using a descriptive qualitative method with Roland Barthes’ semioticapproach, data were collected through documentation and note-taking techniques.Analysis was conducted in two stages: heuristic (denotative meaning) andhermeneutic (connotative and symbolic meaning). Findings show that the lyricshave a strong poetic structure—featuring diction, imagery, and figurativelanguage—and express deep emotional and universal themes. The semioticanalysis identifies Barthes’ five codes: hermeneutic, semic, symbolic, proairetic,and cultural, forming an intricate web of meaning. The study concludes that thealbum combines linguistic beauty with humanist messages relevant tocontemporary life, highlighting the literary value of popular music. Future researchcould explore visual elements or apply other semiotic theories for broader insights.